1995
DOI: 10.1046/j.1471-4159.1995.64031390.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl Radical‐Mediated Oxidation of Serotonin: Potential Insights into the Neurotoxicity of Methamphetamine

Abstract: When incubated with a hydroxyl radical (HO•)‐generating system (ascorbic acid/Fe2+‐EDTA/O2/H2O2), 5‐hydroxytryptamine (5‐HT; serotonin) is rapidly oxidized initially to a mixture of 2,5‐, 4,5‐, and 5,6‐dihydroxytryptamine (DHT). The major reaction product is 2,5‐DHT, which at physiological pH exists as its keto tautomer, 5‐hydroxy‐3‐ethylamino‐2‐oxindole (5‐HEO). Rapid autoxidation of 4,5‐DHT gives tryptamine‐4,5‐dione (T‐4,5‐D), which reacts with the C(3)‐centered carbanion of 5‐HEO to give 3,3′‐bis(2‐aminoet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 32 publications
(46 reference statements)
0
41
1
Order By: Relevance
“…While the indole structure of serotonin is less susceptible to quinone formation, the addition of a hydroxyl group creates the possibility for further oxidation to an ortho-or metaquinone, causing adduction to macromolecules and terminal destruction [185]. Injection of 5,6-dihydroxytryptamine or 5,7-dihydroxytryptamine destroys serotonin neurons, and it has been suggested that serotonin can be oxidized to these compounds in vivo [186][187][188]. Experimental evidence suggests that in Alzheimer's disease and disorders of copper storage, serotonin oxidation produces 4,5-dihydroxytryptamine which further oxidizes to compounds that inhibit acetylcholine esterase and cause oxidative stress [189][190][191][192].…”
Section: Vesicular Transport and Neurotransmitter Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…While the indole structure of serotonin is less susceptible to quinone formation, the addition of a hydroxyl group creates the possibility for further oxidation to an ortho-or metaquinone, causing adduction to macromolecules and terminal destruction [185]. Injection of 5,6-dihydroxytryptamine or 5,7-dihydroxytryptamine destroys serotonin neurons, and it has been suggested that serotonin can be oxidized to these compounds in vivo [186][187][188]. Experimental evidence suggests that in Alzheimer's disease and disorders of copper storage, serotonin oxidation produces 4,5-dihydroxytryptamine which further oxidizes to compounds that inhibit acetylcholine esterase and cause oxidative stress [189][190][191][192].…”
Section: Vesicular Transport and Neurotransmitter Toxicitymentioning
confidence: 99%
“…Experimental evidence suggests that in Alzheimer's disease and disorders of copper storage, serotonin oxidation produces 4,5-dihydroxytryptamine which further oxidizes to compounds that inhibit acetylcholine esterase and cause oxidative stress [189][190][191][192]. Furthermore, the production of neurotoxic oxidation products of cytosolic serotonin has been proposed as a possible mechanism of methamphetamine neurotoxicity in these neurons [187,191,193].…”
Section: Vesicular Transport and Neurotransmitter Toxicitymentioning
confidence: 99%
“…The mechanism underlying the development of serotonergic neurotoxicity is unclear. Endogenous formation of 5,6-dihydroxytryptamine due to 5-HT excess release following the administration of substituted amphetamines (Commins et al 1987), and the generation of other products of 5-HT oxidation (Wrona et al 1995) may be involved in degeneration of 5-HT nerve terminals.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism underlying the development of serotonergic neurotoxicity is unclear. Endogenous formation of 5,6-dihydroxytryptamine due to 5-HT excess release following the administration of substituted amphetamines (Commins et al 1987), and the generation of other products of 5-HT oxidation (Wrona et al 1995) may be involved in degeneration of 5-HT nerve terminals.Other amphetamine analogs, such as methamphetamine (METH) and 3,4-methylenedioxy-methamphetamine (MDMA) cause varying degrees of dopaminergic and serotonergic neurotoxicity, depending on the species examined. Evidence suggests the involvement of free radicals and, specifically, reactive oxygen species in amphetamines-induced dopaminergic neurotoxicity (Cadet and Brannock 1998;Hanson et al 1998).…”
mentioning
confidence: 99%
“…This may not be surprising when one considers that . OH-mediated oxidation by nonenzymatic procedures in vitro (e.g., by ascorbic acid/Fe 2+ -EDTA/O 2 /H 2 O 2 ,) results in the formation of a number of products (2,5-DHT, 4,5-DHT, 5-OH-3-ethylamino-2-oxoindole, 5-HEO, tryptamine-4,5-dione) among which 5,6-DHT was only a minor, unstable component (Wrona et al, 1995a). Similar intermediates are generated by electrochemically driven and tyrosinase-O 2 -mediated oxidation (the enzyme that catalyzes 5,6-o-indolequinone formation from SERT in melanocytes).…”
Section: Chemical Properties Of Neurotoxic Hydroxylated Phenyl-and Inmentioning
confidence: 99%